Monitoring of Boundaries of Immovable Objects of Historical and Cultural Heritage by Cartometric Method - Chetverikov, B. V.; Trevoho, I. S. (Ukrainian Geographical Journal, 2024)
Today, the most effective methods for studying polygonal objects of historical and cultural heritage are cartometric and remote sensing methods (mainly based on the processing of remote sensing data). If necessary, also use archeology, but only after using the specified methods. This work presents the application of the cartometric method using GIS technologies to determine the boundaries of Jewish cemeteries in the village of Gornostaypil, Kyiv region, located on the border of the Chernobyl 30-kilometer exclusion zone, and in the village of Olyka, Volyn region. Today, the cemetery’s grounds are not used for burials. In the Soviet period, in the village of Gornostaypil, administrative and economic buildings were built, and in the village of Olyka, partly by the private sector. Both archival and modern cartographic products and remote sensing data served as input data. Thus, all cartographic products are small-scale. Due to the display of objects and the generalization of the borders and areas of cemeteries, they are distorted, so the study of the dynamics of the elevation of cemeteries conditions their use. To display the historical boundaries of objects in the modern urban planning picture, plans of cemeteries on a scale of 1:500 were created using geodetic methods using GNSS surveying.